The Impact Of E-Government System Implementation On Employee Productivity In The Department Of Population And Civil Registration Of Bandung City - Nurhasanah; Dina; Heri; Gunawan Undang (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This research focuses on the influence of e-government implementation on employee performance in the Department of Population and Civil Registration of Bandung City. Using a quantitative associative method, the study involved 71 respondents as the sample. The results show a very strong influence of e-government on employee performance, with a correlation coefficient of 0.994. Supporting factors include adequate infrastructure and an efficient work culture. The researchers recommend recruiting IT-background human resources and conducting more intensive training to improve employees' understanding and performance related to e-government. Keywords: E-goverment; perfomance; employees